Determinants of tuberculosis among adult people living with HIV on antiretroviral therapy at public hospitals in Hawassa City, South Ethiopia - Asefa, Ahmed; Bolka, Habte; Woldesemayat, Endrias Markos (Frontiers in Epidemiology, 2024)
Background The burden of tuberculosis (TB)/HIV co-infection is high in sub-Saharan African countries. The aim of the present study was to identify determinants of TB among people living with HIV (PLHIV) on antiretroviral therapy (ART) at public hospitals in Hawassa City Administration, Sidama Region, Ethiopia. Methods A facility-based case-control study was conducted between 30 March and 30 April 2023. We employed a systematic random sampling to recruit participants. The cases were all adult PLHIV who developed TB after ART initiation, and the group without TB were all adult PLHIV who did not develop TB after their ART initiation. Data were collected from patients’ medical records using Kobo-tool and then exported to SPSS Version 26 for analysis. A multivariable logistic regression was used to identify the predictors of TB. Statistical significance was defined using the 95% confidence interval (CI). Result A total of 124 cases and 249 people without TB participated in the study. In a multivariable logistic regression analysis, we identified five independent determinants of TB. These include age (adjusted odds ratio (AOR) = 2.7; 95% CI 1.4–5.2), patients’ residency (AOR = 6.4; 95% CI 2.8–14.5), WHO clinical stage III or IV (AOR = 6.7; 95% CI 3.2–14.0), isoniazid plus rifapentine (3HP) prophylaxis using (AOR = 0.5; 95% CI 0.2–0.9), and having other opportunistic infections (AOR = 3.6; 95% CI 1.7–7.6). Conclusion and recommendation Several risk factors for TB were identified among PLHIV. Strengthening TB screening in advanced disease conditions, encouraging use of 3HP prophylaxis, and early diagnosis and treatment of opportunistic infections were recommended to reduce the incidence of TB among PLHIV.